1997
DOI: 10.1007/s004360050264
|View full text |Cite
|
Sign up to set email alerts
|

Frequency distributions of fish parasites in the perch Perca fluviatilis L. from Lake Constance

Abstract: Seventy perch (Perca fluviatilis) caught in Lake Constance at Langenargen in May 1990 were examined for parasites. The frequency distributions of the eyefluke Diplostomum spathaceum (Rudolphi, 1819), and the tapeworms Proteocephalus percae (Müller, 1780) and Triaenophorus nodulosus (Pallas, 1781) fitted closely to a negative binomial. Only a few fish were highly parasitized. These fishes are devoured by the final hosts: gulls (Diplostomum spathaceum) or the pike (Triaenophorus nodulosus). The fish population w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
(12 reference statements)
1
22
0
Order By: Relevance
“…The observed prevalences are computed for the age classes (0, 1], (1,2], (2,3], (3,4], (4,5], 5+, where 5+ summarizes all sheep older than 5 years. For the age classes 1 − 4, the majority of the observed ages coincide with the end points of the interval.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed prevalences are computed for the age classes (0, 1], (1,2], (2,3], (3,4], (4,5], 5+, where 5+ summarizes all sheep older than 5 years. For the age classes 1 − 4, the majority of the observed ages coincide with the end points of the interval.…”
Section: Resultsmentioning
confidence: 99%
“…The data typically exhibit two well-known features, a substantial proportion of zeros and skewed positive counts [1,2,3], meaning that some hosts harbor many parasites while most have just a few. To analyze such aggregated parasite data, the fitting of the negative binomial distribution is a common method, as in [4] to model the abundance of the fluke Diplostomum spathaceum in fish, in [5] for European red mite on apple leaves, in [6] for the tapeworms Echinococcus granulosus and multilocularis in dogs, in [7] for the nematode Trichinella spiralis in rabbits and in [8] for the larval stage of the mites Allothrombium pulvinum Ewing in lice. However, these models do not take into account the age of the hosts, which is known to influence the parasite pattern [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the overall prevalence of L. angustus and N. agilis was higher in male than in female and juvenile fish, whereas S. obesum showed a higher prevalence in female than male and juvenile fish. Balling and Pfeiffer (1997) reported higher Proteocephalus percae infection in female perch than in males during the spawning period. They also explained that this might be the result of the higher food consumption of females; thus, females are more likely to become infected by copepods.…”
Section: Discussionmentioning
confidence: 99%
“…The dierences observed in infestation with B. luciopercae and I. variegatus were examined with the H-test. The other methods were identical to those applied earlier (Balling and Pfeier 1997).…”
Section: Methodsmentioning
confidence: 99%
“…The question as to whether perch migrate should be examined according to the infestation of a number of dierent and geographically well-separated populations. Since an investigation of the infestation of ®sh from dierent locations at various seasons was missing, we began to study this question (Balling and Pfeier 1997). In perch caught at six dierent sites it was found that various species of digenean trematodes did not behave uniformly during the year; whereas some species showed clear seasonal dierences, others did not.…”
Section: Introductionmentioning
confidence: 99%